Safety first: Factors affecting preceptor midwives experiences of competency assessment failure among midwifery students. (July 2019) - Bradshaw, Carmel; Pettigrew, Judith; Fitzpatrick, Mary
Highlights: Reluctance to fail midwifery students in clinical practice by preceptor midwives is always outweighed by concerns for safety of practice. Failure of clinical practice assessments in midwifery are affected by a multiplicity of factors, many unrelated to student performance. These factors include the increasing complexity of maternity settings, compounded by staff shortages, challenges in operationalising assessment processes and the emotional costs associated with failing a student. Failing a clinical assessment is stressful for both the student and the preceptor midwife and appropriate support needs to be provided to all involved. Preceptorship needs to be valued more particularly from a strategic perspective to recognise preceptors' responsibilities as gatekeepers to the profession of midwifery. Abstract: Background: Assessment of clinical practice is a core component of midwifery education. Clinical assessment is challenging and affected by a number of factors. Preceptor midwives are reported to be reluctant to fail students in clinical assessments. This is worrying as preceptor midwives are gatekeepers to the profession of midwifery and need to ensure midwifery students are safe and competent practitioners of midwifery on completion of their programmes. Methods: This qualitative descriptive study explores preceptor midwives experiences of clinical assessment of midwifery students in four maternity units in the Republic of Ireland. Following ethical approval, twenty-nine preceptor midwives were interviewed. Content analysis was used to analyse the data and two themes with associated subthemes identified. Findings: Competency assessment in practice was supported by a robust, clearly delineated process, considered vital to ensure effective and fair assessment of midwifery students. The process in place had many advantages but attracted some criticism too, most notably language, documentation and lack of continuity of the preceptor. Thechallenges of clinical assessment were multifaceted but the most pressing concern was dealing with students who were struggling in practice where the outcome of an assessment was potentially a fail. Preceptor midwives expressed reluctance to fail students but balanced this with ensuring safety for women and their babies. A number of other challenges hampered decisions in clinical assessments. These included the confidence of the preceptor, juggling the competing demands of clinical practice with effective assessment in an increasingly complex and fiscally challenging environment, operationalising the competency assessment process and the emotional toll associated with failing a student. Conclusion: Preceptors' primary focus is on ensuring that graduate midwives are safe and competent practitioners and it is this which guides their decision making on the outcome of clinical assessments. However, more support is required for the onerous responsibility of clinical assessment, particularly for less experienced midwives but also when failure of clinical assessment is a potential outcome. Preceptorship needs to be valued more at a strategic level.